Between Human Extinction and the Extinction of Good Arguments: Placing Warning Signs for the Survival of Both - Vilaça, Murilo (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
This text is a response to Torres’ article on artificial superintelligence and human extinction. I place some warning signs on the author’s argumentative trajectory, arguing that the topic of human extinction is relevant, so it is necessary to correct the course at several points.